A DESCRIPTIVE ANALYSIS ON THE EXISTENCE OF THE TORANG ART COMMUNICTY IN SULAWESI UTARA - Rondonuwu, Angelia Feren; Mangare, Jans G.; Rantung, Ruly (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
This present study aims at analyzing the existence of the Torang Art Community in North Sulawesi. This research uses qualitative descriptive method which are used to determine and report the existing situation according to reality. In this study, the data collection was carried out by using observation, interview and documentation techniques and supported by data triangulation techniques as data validity. The obtained data are then analyzed descriptively. Ã‚Â The results of this research show that the TORANG art community was declared on November 5, 2018 in Tomohon at the Maria Budiyatmi plenary exhibition formed by several North Sulawesi artists. The existence of the TORANG art community existed only in the early years of this community. Several art activities have been carried out by the TORANG art community, including exhibitions, discussions of works, work reviews, sketches on the spot and several art activities that often complement the exhibition when the exhibition is held such as body painting, live painting, and so on. But currently, according to the data found, the TORANG Art community can be said to have begun to fade or have not been active in art activities for approximately the last year. Then there are also several factors that influence the TORANG Art community, both supporting factors such as a sense of togetherness and mutual care and inhibiting factors such as distance between members and funds in art activities.